Characterization of an Essential RNA Secondary Structure in the 3′ Untranslated Region of the Murine Coronavirus Genome - Hsue, Bilan (American Society for Microbiology, 2000)
We have previously identified a functionally essential bulged stem-loop in the 3′ untranslated region of the positive-stranded RNA genome of mouse hepatitis virus. This 68-nucleotide structure is composed of six stem segments interrupted by five bulges, and its structure, but not its primary sequence, is entirely conserved in the related bovine coronavirus. The functional importance of individual stem segments of this stem-loop was characterized by genetic analysis using targeted RNA recombination. We also examined the effects of stem segment mutations on the replication of mouse hepatitis virus defective interfering RNAs. These studies were complemented by enzymatic and chemical probing of the stem-loop. Taken together, our results confirmed most of the previously proposed structure, but they revealed that the terminal loop and an internal loop are larger than originally thought. Three of the stem segments were found to be essential for viral replication. Further, our results suggest that the stem segment at the base of the stem-loop is an alternative base-pairing structure for part of a downstream, and partially overlapping, RNA pseudoknot that has recently been shown to be necessary for bovine coronavirus replication.